2010
DOI: 10.2527/jas.2009-2326
|View full text |Cite
|
Sign up to set email alerts
|

Correlative responses for carcass and meat quality traits to selection for ovulation rate or prenatal survival in French Large White pigs1

Abstract: Correlated effects of selection for components of litter size on carcass and meat quality traits were estimated using data from 3 lines of pigs derived from the same Large White base population. Two lines were selected for 6 generations on high ovulation rate at puberty (OR) or high prenatal survival corrected for ovulation rate in the first 2 parities (PS). The third line was an unselected control (CON). The 3 lines were kept for a 7th generation, but without any selection. Carcass and meat quality traits wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Phenotypic variation of meat pH is partially regulated by genes as indicated in the review of [2] who reported 0.16 as the average heritability value for pH scored at about 1 hour post mortem (pH1) and 0.21 as the average value for pH recorded at 24 hours post mortem (pHu). Other researches showed that the heritability of pHu in Large White ranged from 0.29 to 0.45 [3,4]. Up to now only two major genes related to pig meat pH have been identified: Ryanodine receptor 1 ( RYR1 ) mapped on Sus scrofa chromosome (SSC) 6 [5] and Protein kinase, AMP-activated, gamma 3 non-catalytic subunit ( PRKAG3 ), located on SSC13 [6].…”
Section: Introductionmentioning
confidence: 99%
“…Phenotypic variation of meat pH is partially regulated by genes as indicated in the review of [2] who reported 0.16 as the average heritability value for pH scored at about 1 hour post mortem (pH1) and 0.21 as the average value for pH recorded at 24 hours post mortem (pHu). Other researches showed that the heritability of pHu in Large White ranged from 0.29 to 0.45 [3,4]. Up to now only two major genes related to pig meat pH have been identified: Ryanodine receptor 1 ( RYR1 ) mapped on Sus scrofa chromosome (SSC) 6 [5] and Protein kinase, AMP-activated, gamma 3 non-catalytic subunit ( PRKAG3 ), located on SSC13 [6].…”
Section: Introductionmentioning
confidence: 99%